Tobacco product prices before and after a statewide tobacco tax increase. Issue 2 (6th January 2015) - Brock, Betsy; Choi, Kelvin; Boyle, Raymond G; Moilanen, Molly; Schillo, Barbara A
Abstract : Background: In 2013, the State of Minnesota Legislature passed a tobacco tax increase that increased the combined cigarette excise and sales tax by US$1.75 (from US$1.60 to US$3.35) and increased the tax on non-cigarette tobacco products from 70% to 95% of the wholesale price. The current study explores the change in tobacco prices in retail locations and whether the tax increase was fully passed to consumers. Methods: An observational study of tobacco retail prices was performed in a sample of 61 convenience stores in Minnesota, North Dakota, South Dakota and Wisconsin. Six rounds of data were collected between May 2013 and January 2014. In each round, purchases were made at the same stores for the same four tobacco products (Camel Blue cigarettes, Marlboro Gold cigarettes, Grizzly Wintergreen moist smokeless tobacco and Copenhagen Wintergreen moist smokeless tobacco). Results: For all studied tobacco products, prices in Minnesota increased significantly after the tax increase (Round 1–Round 6). After controlling for price changes in neighbouring states, the average price difference in Minnesota for the two cigarette brands increased by US$1.89 and US$1.81, which are both more than the US$1.75 tax increase. For moist smokeless, the average price difference increased by US$0.90 and US$0.94. Significant price changes were not observed in the comparison states. After the introduction of the minimum moist smokeless tax, a significantly higher proportion of Minnesota stores offered price promotions on smokeless tobacco. Conclusions: A large tobacco tax resulted in an average retail cigarette price exceeding the tax, suggesting the industry over-shifted the cigarette tax increase to consumers in Minnesota. The findings support the known public health benefit of tobacco tax increases while highlighting the need for additional information about how, or if, tobacco companies use price promotions to blunt the impact of tax increases.